Estimating helminth burdens using sibship reconstruction - Neves, M. Inês (Parasit Vectors, 2019)
BACKGROUND: Sibship reconstruction is a form of parentage analysis that can be used to identify the number of helminth parental genotypes infecting individual hosts using genetic data on only their offspring. This has the potential to be used for estimating individual worm burdens when adult parasites are otherwise inaccessible, the case for many of the most globally important human helminthiases and neglected tropical diseases. Yet methods of inferring worm burdens from sibship reconstruction data on numbers of unique parental genotypes are lacking, limiting the method’s scope of application. RESULTS: We developed a novel statistical method for estimating female worm burdens from data on the number of unique female parental genotypes derived from sibship reconstruction. We illustrate the approach using genotypic data on Schistosoma mansoni (miracidial) offspring collected from schoolchildren in Tanzania. We show how the bias and precision of worm burden estimates critically depends on the number of sampled offspring and we discuss strategies for obtaining sufficient sample sizes and for incorporating judiciously formulated prior information to improve the accuracy of estimates. CONCLUSIONS: This work provides a novel approach for estimating individual-level worm burdens using genetic data on helminth offspring. This represents a step towards a wider scope of application of parentage analysis techniques. We discuss how the method could be used to assist in the interpretation of monitoring and evaluation data collected during mass drug administration programmes targeting human helminthiases and to help resolve outstanding questions on key population biological processes that govern the transmission dynamics of these neglected tropical diseases.